Perancangan Aplikasi Penjadwalan Praktek Dokter di Rumah Sakit Menggunakan Metode Pewarnaan Graf: Designing a Doctor's Practice Scheduling Application in a Hospital Using the Graph Coloring Method - Marian Tonis; Abdul Zaky; Marido Bisra; Wiwik Suryandartiwi (LPPM STIKES Guna Bangsa Yogyakarta, 2024)
Scheduling is a common need nowadays. One example is hospitals. Hospitals need a scheduling process to schedule doctors who will be on duty and use a room. This is due to the large number of doctors and the limited number of rooms, so a scheduling system is needed as needed. Problems that occur at Petala Bumi Hospital, the number of doctors on duty in the emergency room is quite large. However, there is confusion from management in managing the schedule of doctors in the emergency room. This research is a development of the Graph coloring method carried out in the preparation of a doctor's schedule at the hospital. This research was conducted to overcome scheduling problems that are often inappropriate and usually need to be corrected repeatedly in hospitals. The methods used to perform scheduling are quite diverse, one of which is the Graph coloring method. This study aims to determine the application of graph coloring in compiling a doctor's schedule. This research is a type of R&D research with a system design design with the application of graph coloring. Graph coloring is done for four days because the graph coloring pattern matrix repeats after the fourth day. During the four-day preparation, graph coloring has 10 colors or chromatic numbers assuming three shifts and two doctors in one shift. Therefore, the optimization of the doctor's schedule preparation at the Emergency Room of Petala Bumi Hospital can be done with at least 10 doctors